A Fumbled Opportunity? A Case Study of Twitter's Role in Concussion Awareness Opportunities During the Super Bowl. (February 2015) - Hull, Kevin; Schmittel, Annelie
Doctors, journalists, and other advocates are attempting to draw attention to the dangers of head trauma in football, and the popularity of social media has given them a new outlet to perform advocacy. This case study explores how advocates for concussion awareness in football used Twitter to help spread their message during the 2013 Super Bowl. A content analysis of tweets from 92 concussion advocates on the day of the Super Bowl was conducted. Analysis revealed that the advocates used Twitter for (a) linking to football concussion content, (b) Super Bowl game-related commentary, (c) non-concussion or non–Super Bowl related links or messages, (d) linking to non-football concussion content, (e) concussion-related commentary, (f) engagement, and (g) self or website promotion. Results demonstrate that while advocates have a tremendous opportunity to use the agenda-setting possibilities that are afforded through Twitter, concussion advocates did not utilize Twitter in this manner.